Study of Clinical Profiles, Risk Factors and Coronary Angiographic Patterns in Female Patients Presenting with Anginal Chest Pain in a Tertiary Care Centre of Nepal - Adhikari, Suman; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Thapa, Sanjeev; Devkota, Surya; Manandhar, Bhawani; Khanal, Rajaram; Shakya, Smriti; Yadav, Vijay; Sharma, Manju; Sahi, Ravi; et al. (Nepalese Heart Journal, 2022)
Background and Aims: Coronary artery disease is one of the important causes of deaths in females in many countries. Females with chest pain are more likely to be treated in a different way as compared to males at the time of presentation. Worldwide, there has been a considerable rise in the number of females who are undergoing coronary angiography recently. Methods: This study was a single-centre, prospective, observational study conducted in the department of cardiology, MCVTC, Tribhuvan University, Nepal. The study period was from 5th July 2020 to 4th July 2021.155 female patients with anginal chest pain were enrolled. Data were collected after thorough history taking, physical examination, laboratory investigations, and coronary angiography. They were further divided into three age groups:<50 years,50-65 years and >65 years. Subsequently statistical analysis was done using latest version of SPSS. Results: The mean age of the patients was 59.64 years (SD=11.428). There were 119 (76.77%) postmenopausal patients. The most prevalent risk factor of IHD was HTN (43.87% ). Obesity/overweight was most common (58.62%) in those with age <50 years. DM was most common (26.32%) in age group 50-65 years. HTN was the most prevalent (52.63%) in age group 50-65 years. The maximum proportion of dyslipidemic patients (34.21%) were found in age group 50-65 years. 52.25% patients presented with acute coronary syndrome. 33.55% patients had normal coronary arteries. 11.61% patients had nonobstructive coronary artery disease. Obstructive coronary artery disease was found in 51.61% patients. IN patients with obstructive CAD, LAD was the most commonly involved vessel followed by RCA . Conclusion: Findings from our study shows higher prevalence of risk factors for IHD in Nepalese females. This study also demonstrates that as females get older and become postmenopausal, the number of risk factors for CAD increases. Understanding the risk factors for CAD and angiographic patterns in females could be helpful in implementing optimal treatment strategies in females with angina.